Effects of restriction of wild herbivore movement on woody and herbaceous vegetation in the Okavango Delta Botswana. (11th January 2013) - Cassidy, Lin; Fynn, Richard; Sethebe, Bongani
Abstract: We conducted herbaceous and woody vegetation surveys across Botswana's southern Okavango Buffalo Fence, which separates wildlife management from tribal grazing areas, to determine whether the restriction of herbivore movement by fencing has influenced vegetation composition, diversity and structure. We sampled herbaceous and woody vegetation at twenty paired sites every 2 km along the fence. For the herbaceous layer, ten 0.25 m 2 quadrats were laid every 10 m perpendicular to the fence; while for the woody vegetation, variable quadrat plots were used. Paired t ‐tests were run. Results show little difference in forb or grass composition between the two sides. However, the cover and diversity of many woody species were greatly reduced across most height classes on the wildlife management side. Overall woody cover on the wildlife side of the fence was nearly half that of the tribal grazing side ( t = 2.83, P = 0.011, df = 19), while overall wood diversity was also significantly less on the wildlife side ( t = 3.29, P = 0.004, df = 19). We conclude that the concentration of wildlife due to the fence, while improving habitat for some herbivore species, is having a detrimental effect on plant diversity in general.